Traumatic dental injuries among 12- and 15-year-old adolescents in Georgia: results of the pathfinder study - Bilder, Leon; Margvelashvili, Vladimer; Sgan-Cohen, Harold; Kalandadze, Manana; Levin, Liran; Ivanishvili, Rusudan; Machtei, Eli E. (Dental traumatology, 2016)
Background Traumatic dental injuries (TDI) are a widespread pathology with serious dental public health concerns. Objectives The aim of this pathfinder study was to collect initial epidemiological data on oral health in Republic of Georgia. As part of this study, the prevalence and severity of TDI in permanent teeth among seventh‐ and tenth‐grade schoolchildren were evaluated. Methods Schoolchildren were examined in four schools in the capital city of Tbilisi, two schools in two other major cities, and one school in four additional villages. In addition to demographical data, the following parameters were collected and recorded: Overjet (OJ), lip competence, number and type/location of the teeth with TDI and Type of TDI. The study population comprised of children aged 12 (seventh grade) and 15 years old (10th grade). Results A total of 823 7th‐ and 10th‐grade schoolchildren were examined. The overall prevalence of TDI among Georgian population was found to be 10.4% (86 children). The prevalence of TDI was greater in the older age cohort (P < 0.05). Lip posture did not seem to have a marked effect on TDI. Children with an OJ greater than 5 mm were more likely to present with dental injuries compared to children with an OJ equal to or smaller than 5 mm (P < 0.05). Children from rural areas presented with greater prevalence of TDI compared to their urban counterparts (P < 0.05). The maxillary central incisors were the most common teeth to be affected by trauma accounting for 85.2% of the TDI cases. Enamel fracture was the main type of TDI (91.3%). Conclusions The prevalence of TDI in Georgian schoolchildren, as presented in this survey, population was found to be rather moderate and involved mainly minor superficial injuries. Rural communities have shown in this report substantial higher rates; thus, educational program might be directed mostly to these regions to children, teachers, and healthcare providers.